Implementation and evaluation of an Integrated Wireless System for smart home - Mohammad Radzuan, Ahmad bakari; Mohamad Fauzee, Faizal Azreen; Hassan Abdalla Hashim, Aisha; Daoud, Jamal Ibrahim (2012)
Integrated Wireless System for Smart Home is a device responsible for remotely monitoring and controlling the activity inside a house. The system has the ability to notify users of all the activity of electrical/ electronic devices connected within the house area to the system regardless of the geographic vicinity of the user and his house. Users are able to send command to the system either using SMS or Bluetooth. The system is able to automatically change the controlling module according to the threshold of the Bluetooth control system. This paper discusses the implementation and the evaluation of the proposed system. The result shows that the proposed system performs well while having low cost.